2016
DOI: 10.1371/journal.pone.0162097
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Mortality after Hip Fracture Surgery: A 3 Years Follow Up

Abstract: Background and AimsTo determine mortality rates and predisposing factors in patients operated for a hip fracture in a 3-year follow-up period.MethodsThe study included patients who underwent primary surgery for a hip fracture.The inclusion criteria were traumatic, non-traumatic, osteoporotic and pathological hip fractures requiring surgery in all age groups and both genders. Patients with periprosthetic fractures or previous contralateral hip fracture surgery and patients who could not be contacted by telephon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 27 publications
(48 reference statements)
5
34
0
Order By: Relevance
“…The highest impact of cognitive impairment was seen during the first three months. This observation confirms the results from other studies and may—at least partly—be explained by the rehabilitation difficulties in patients with cognitive impairment . We were surprised to find a 2‐3 times enhanced mortality in the subgroup with MCI (CDR:0.5), reflecting a level of cognitive impairment, which generally remains unnoticed in the social context.…”
Section: Discussionsupporting
confidence: 90%
“…The highest impact of cognitive impairment was seen during the first three months. This observation confirms the results from other studies and may—at least partly—be explained by the rehabilitation difficulties in patients with cognitive impairment . We were surprised to find a 2‐3 times enhanced mortality in the subgroup with MCI (CDR:0.5), reflecting a level of cognitive impairment, which generally remains unnoticed in the social context.…”
Section: Discussionsupporting
confidence: 90%
“…3 Independent Discussion: Reducing mortality in this population may prove challenging given the urgent nature of surgery and comorbidity-driven risk factors. 10,11 Surgical factors (e.g. bone cementation 11 ) could be further explored.…”
Section: Strengths Original Discussion: '1) the Study Was A Randomizementioning
confidence: 99%
“…Comorbidity burden may be a significant driver of postoperative mortality after hip fracture, as demonstrated here and in prior investigations. 10,11 Commentary: In the Original Discussion, the investigators focus on reasons why the findings of the current study were different from a smaller previous study with a similar design done by the same team. 6 The Independent Discussant notes that while there has been little research examining whether depth of sedation affects outcomes after hip fracture surgery, several clinical trials and observational studies have investigated whether the outcomes are different after general anaesthesia vs regional anaesthesia.…”
mentioning
confidence: 86%
“…Age and male sex (9) and general anesthesia and time before surgery (10) were suggested as the primary factors causing high mortality rates. However, some other studies have reported contrasting results (11)(12)(13).…”
Section: Introductionmentioning
confidence: 94%